Analisis Kesulitan Guru dalam Mengimplementasikan Pembelajaran Tematik pada Kurikulum Merdeka di Sekolah Dasar - Sri Enggar Kencana Dewi; Ratih Purnama Pertiwi; Supangat Supangat; Ahmad Ulin Ni’am; Devi Rahmawati (IBTIDA', 2023)
The government is currently very concerned about the development of education in Indonesia. In the previous year, the government had just updated the curriculum for the sake of reforming education in Indonesia. The curriculum, 2013 curriculum hopes to provide a new learning system. In the curriculum, the learning was thematic, which at that time became a pro and con for teachers. After the curriculum was implemented, all educational institutions in Indonesia, the government re-evaluated and looked at its output in society. Then now the government issued a new curriculum, namely the independent curriculum, which must have a difference from the previous learning system. Of course, the existence of this new curriculum has many difficulties for teachers in its implementation. This study aims to analyze the independent curriculum. This research method is descriptive qualitative research. Data collection techniques in this study are interviews and documentation. The step taken by analyzing is compiling data systematically, describing, selecting, and sorting important data, and making conclusions. Based on the research conducted the difficulties often experienced by teachers are such early planning of the learning process that is poorly prepared such as by filling in the platform that has been provided without adequate guidance and preparing learning tools that they have not mattered, such as the teaching module the second in The implementation of the learning process, for example, the delivery of good learning materials has not used much media or other supporting tools, especially the application of learning projects, and the last is in evaluating the end of the learning process that has begun to run.